Quasi-satellite system for leader-follower spacecraft formation - Mohd Harithuddin, Ahmad Salahuddin (Institute of Physics Publishing, 2016)
The quasi-satellite motion is where a celestial body appears to orbit around another body that is also orbiting a common focus. The recent discoveries of asteroids in quasi-satellite motion around the Earth inspired this work. This paper attempts to look into exploiting the quasi-satellite dynamics in nature to provide a new perspective in spacecraft formation flight. We consider a two-spacecraft formation flight in which the follower appears to orbit of the leader in its reference frame. We perform a parametric analysis by varying the orbital elements of leader and follower examine the initial conditions needed to simulate a quasi-satellite formation system. We illustrate the trajectories of the follower spacecraft. This serves two purposes: firstly, to demonstrate formation flight based on the idea of quasi-satellite; and secondly, to gain some insights on the shapes of the resultant "quasi-orbits".